Princess Mononoke Understanding Studio Ghibli's Monster Princess - Denison, Rayna (Animation: Key Films/Filmmakers, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Princess Mononoke (1997) is one of anime's most important films. Hayao Miyazaki's epic fantasy broke domestic box office records when it came out in Japan, keeping pace with the success of Hollywood films like Titanic (1997). Princess Mononoke was also the first of Studio Ghibli's films to be distributed outside Japan as part of a new deal with Disney subsidiary Buena Vista International. Coinciding with the 20th anniversary of the release of the film, Rayna Denison curates this new collection to critically reflect on Princess Mononoke's significance within and beyond Japanese culture. The collection investigates the production, and re-production, processes involved in the making of Princess Mononoke into a global phenomenon and reevaluates the film's significance within a range of global markets, animation techniques, and cultures. In revisiting this undeniably important film, the collection sheds light on the tensions within anime and the cultural and social issues that Princess Mononoke explores, from environmental protection to globalization to the representation of marginalized groups. In this remarkable new collection, Princess Mononoke is examined as a key player during a major turning point in Japanese animation history.